2018
DOI: 10.5539/jel.v7n2p221
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Relationship between Pre-school Children’s and Their Teachers’ Attitudes and Awareness towards the Environment

Abstract: The purpose of this study is to determine the level of awareness and attitudes towards environment of pre-school children's and their teachers' and to examine the relationship between them. This study was based on correlational research model. The study group consisted of 26 pre-school teachers working in kindergartens and primary schools in a province, and 208 children in the 5-6 age groups in which these teachers entered their classes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Education is required to be able to improve the quality of a person so that they have high competitive achievements (Yuliyani et al, 2017;Syam, 2019;Kosim, 2020). Education is very important for everyone to form attitudes and selfcharacter (Buldur & Omeroglu, 2018;Darmaji et al, 2019;Suastra et al, 2017). Through education, there is a process of character formation in every human being.…”
Section: Introductionmentioning
confidence: 99%
“…Education is required to be able to improve the quality of a person so that they have high competitive achievements (Yuliyani et al, 2017;Syam, 2019;Kosim, 2020). Education is very important for everyone to form attitudes and selfcharacter (Buldur & Omeroglu, 2018;Darmaji et al, 2019;Suastra et al, 2017). Through education, there is a process of character formation in every human being.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this research revealed that the majority of students were aware of the importance of environmental education in the preschool period (Table 7), but preservice primary school teachers indicated a higher level of importance than preservice preschool teachers. According to Buldur and Ömeroğlu (2018), childhood is a period of very intense development during which attitudes and awareness are formed and developed. The preschool period is crucial because in this period the attitudes of individuals towards the environment are created (Wilson, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The quality and orientation of education demand the Indonesian people's orientation of education in Indonesia, namely, attitudes, intelligence, and competitive achievements (Rahmawati, 2018;Syam, 2019;Kosim, 2020). Education has a fundamental goal, namely character building (Suastra, 2017;Buldur, 2018;. Through this education, there is a process of character building in every human being, one of which is through science subjects in junior high school.…”
Section: Introductionmentioning
confidence: 99%